EARLY PALEOLITHIC FINDS IN THE EUPHRATES VALLEY (SOUTH-EAST ERN TURKEY) IN THE LIGHT OF INITIAL SETTLEMENT OF POPULATION IN ASIA MINOR AND THE CAUCASUS - Ozherelyev, D. V.; Trifonov, V. G.; Celik, H. Z.; Trikhunkov, Ya. I.; Frolov, P. D.; Simakova, A. N. (Izdatelstvo Nauka, 2018)
Early Paleolithic finds older than Acheulean in Eastern Anatolia have been practically unknown until recently. During reconnaissance performed by the joint Russian-Turkish expedition in 2014-2016 several Early Paleolithic stratified locations were found in the Euphrates valley. The stone artifacts collected include choppers, pikes, tools with retouch and blades. Similar stone industries dated to the first half of the Early Pleistocene have been discovered in the Caucasus (Armenia, Dagestan). Besides archaeological typological dating, the Early Pleistocene age of the finds is validated by geomorphological, stratigraphic, paleontological and paleomagnetic data. Some of these locations are dated earlier than Olduvai subchron, i.e. around two million years ago. New discoveries of the Early Paleolithic in Eastern Turkey may have a paramount importance for studying the earliest human culture of the Near East and the Caucasus. Other finds include stone artifacts of the Acheulean and the Middle Paleolithic and can be used to date younger river terraces.
Keywords: Early Paleolithic; Early Pleistocene; the Euphrates; Oldovan; dating and periodization